2012
DOI: 10.4049/jimmunol.1200451
|View full text |Cite
|
Sign up to set email alerts
|

B Cell Memory to a Serogroup C Meningococcal Conjugate Vaccine in Childhood and Response to Booster: Little Association with Serum IgG Antibody

Abstract: The maintenance of adequate serum Ab levels following immunization has been identified as the most important mechanism for individual long-term protection against rapidly invading encapsulated bacteria. The mechanisms for maintaining adequate serum Ab levels and the relationship between Ag-specific memory B cells and Ab at steady state are poorly understood. We measured the frequency of circulating serogroup C meningococcal (MenC)-specific memory B cells in 250 healthy 6- to 12-y-old children 6 y following Men… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
15
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 52 publications
3
15
1
Order By: Relevance
“…Despite this, current oral cholera vaccines achieve lower protective efficacy and shorter duration of protection in young children than in older persons (6). Young children generally respond poorly to polysaccharide antigens (25)(26)(27). Previously, we demonstrated that memory B cell responses in young children to both the T cell-dependent antigen CTB and the T cell-independent antigen LPS following vaccination were significantly lower than those achieved after natural infection (17).…”
Section: Discussionmentioning
confidence: 99%
“…Despite this, current oral cholera vaccines achieve lower protective efficacy and shorter duration of protection in young children than in older persons (6). Young children generally respond poorly to polysaccharide antigens (25)(26)(27). Previously, we demonstrated that memory B cell responses in young children to both the T cell-dependent antigen CTB and the T cell-independent antigen LPS following vaccination were significantly lower than those achieved after natural infection (17).…”
Section: Discussionmentioning
confidence: 99%
“…47 While some studies have demonstrated a relationship between B MEM and antibody concentration at various intervals after immunization this has not been consistent for all antigens or between studies. 9 Blanchard Rohner et al found that B MEM levels rather than antibody levels following priming with MenCCV better discriminated those with putative protective antibody levels at 12 mo. 5 Another study identified a weak positive correlation between 5 mo B MEM levels and 12 mo antibody concentrations for serotypes C and Y but not A or W in children vaccinated at 2 and 4 mo of age with the MenACWY-CRM 197 conjugate vaccine.…”
Section: Correlation Of B Cell Responses To Antibody Concentrationsmentioning
confidence: 99%
“…Figure 2 combines data from the studies discussed in this section to summarize the B MEM response to vaccination in primed and unprimed individuals. [5][6][7][8][9] Frequency of Polysaccharide-…”
Section: Memory B Cell Kineticsmentioning
confidence: 99%
See 1 more Smart Citation
“…While ex vivo assays have shown that B cells are constitutively activated in cGVHD, 115, 116 B lymphopenia and humoral immune deficiency are distinctive characteristics of cGVHD. 117120 .…”
Section: Section 2 Immune Reconstitution In the Laboratorymentioning
confidence: 99%